Оценка влияния изменений одного из входных параметров на процесс ректификации бензилбензоата на колонном оборудовании (метод дисперсионного анализа) - Анохин, Г. О.; Сулима, А. М.; Доильницина, Л. П.; Шепотько, И. П.; Шостак, В. В.; Муратова, Н. А. (НТУ "ХПИ", 2004)
In the clause there is given a method of mathematical statistics (one-factor dispersion analysis), what has allowed to define a degree of the influence of the controllable factor on a result according selective data of the final rectification process.
Keywords: групповые дисперсии; критическая точка; бензил бензоата; гипотеза; коэффициент детерминации